International mathematical olympiads 1959-1977 - Greitzer, Samuel L. (New mathematical library, 2012)
Every year 100 of the most mathematically talented high school students in the country compete in the USA Mathematical Olympiad (USAMO). The USAMO is the third stage of a three-tiered mathematical competition for high school students in the United States and Canada that begins with the AHSME taken by over 400,000 students, continues with the American Invitational Mathematics Exam involving 2,000 students, and culminates with the 100-contestant USAMO. Winners of the USAMO go on to compete in the International Mathematical Olympiad. Compilation of 116 problems of arresting ingenuity given to high school students competing in the International Mathematical Olympiads. All are accessible to secondary school students. The alternative solutions are particularly interesting because they show that there are many ways to solve a problem.